P14.55 Quantitative muscle mass biomarkers are independent prognosis factors in primary central nervous system lymphoma: the role of L3-Skeletal Muscle Index and temporal muscle thickness. (9th September 2021) - Leone, R; Sferruzza, G; Calimeri, T; Steffanoni, S; Conte, G; De Cobelli, F; Falini, A; Ferreri, A; Anzalone, N
Abstract: BACKGROUND: Appropriate patient stratification is of paramount importance in patients with primary central nervous system lymphomas (PCNSL) in order to improve therapeutic choices and to reduce treatment-related neurotoxicity. Age and performance status, two widely used prognostic indicators, may not be the most appropriate parameters for an optimal patient stratification, as age seldom reveals the true biological frailty of a patient and performance status scores are subject to inter-rater variability. Quantitative muscle biomarkers such as the skeletal-muscle-index at the third lumbar vertebra (L3-SMI) and temporal muscle thickness (TMT) are associated with worse prognosis in several oncological diseases. We aim to evaluate the role of these biomarkers in predicting survival in patients with PCNSL undergoing high-dose methotrexate-based chemotherapy. MATERIAL AND METHODS: L3-SMI and TMT were calculated on abdominal CT and brain high-resolution 3D-T1-weighted-MR images, respectively, using predefined validated methods. Standardized sex-specific cut-offs were used to divide patients in different risk categories. Kaplan-Meier plots were calculated, and survival analysis was performed using log-rank tests, univariate, and multivariable Cox-regression models, calculating hazard ratios (HR) and 95% confidence intervals (CI), also adjusting for potential confounders (age, sex, and performance status). RESULTS: Forty-three patients were included in this study. Median follow-up was 23 months (interquartile range 12–40); at median follow-up, rates of progression-free and overall survival for the cohort were 46% and 57%, respectively. Thirteen (30%) and 11 (26%) patients showed L3-SMI or TMT values below the predefined cut-offs. Subgroup analyses showed a significant association between quantitative muscle mass biomarkers and progression-free and overall survival. One-year progression free and overall survival rates were 8% and 21% for the 13 patients with L3-SMI below the standard cut-off value, respectively, compared to 66% and 68% for the 30 patients with L3-SMI above the cut-off values. Likewise, one-year progression free and overall survival rates were 10% and 15% for the 11 patients with low TMT, respectively, compared to 61% and 70% for the 32 patients with high TMT. In Cox-regression multivariable analysis patients with low L3-SMI or TMT showed significantly worse progression-free (HR 4.40, 95%CI 1.66–11.61, p = 0.003; HR 4.40, 95%CI 1.68–11.49, p=0.003, respectively) and overall survival (HR 3.16, 95%CI 1.09–9.11, p = 0.034; HR 4.93, 95%CI 1.78–13.65, p=0.002, respectively) compared to patients with high L3-SMI or TMT. CONCLUSION: Quantitative muscle mass evaluation assessed by both L3-SMI and TMT is a promising tool to identify PCNSL patients at high risk of negative outcome. Confirmatory studies on larger independent series are warranted.